Simultaneously Measured Photoluminescent and Conductive Properties of Printed ZnO Nanocrystals under Ar/O2 Mixtures. (2015) - Nguyen, V.S.; Champouret, Y.; Kahn, M.L.; Jubera, V.; Debéda, H.
Abstract: In this work, both optical and electrical responses of screen-printed metal oxide gas sensors are measured under different Ar/O2 mixtures at room temperature. Printed gas sensors are based on ZnO nanocrystals deposited and further sintered at 400 °C on interdigitated Pt electrodes. The ZnO∼5 nm nanoparticles synthetized by an organometallic route form aggregates after deposition and present surface defects observed on photoluminescence (PL) spectrum. Current and PL intensity variations are simultaneously compared under Ar/O2 mixtures at room temperature. The sorption kinetics appear to be clearly different, with higher sensitivity for electrical conduction but unstable signal and longer time responses.